Learning Number Rounding Based on Project-Based Learning (PJBL) in Elementary School - Marlina Marlina; Mariana Mariana (Universitas Tanjungpura, 2022)
This study aims to improve students' knowledge and understanding of rounding numbers through project-based learning (PjBL). The method was Classroom Action Research (CAR). CAR is a way of determining how to do it with cycles. The participants were 51 fifth grade students in elementary school. In cycle 1, 31 students passed with a Percentage of 51% and those who have not passed amounted to 20 students with a percentage of 39%. Then, continued to cycle II applying the PJBL Model. The result was 47 Students passed with a Percentage of 97% and those who have not passed amounted to 4 students with a percentage of 3%. Through the implementation of PJBL Model, the understanding of rounding numbers in mathematics learning can be accepted because of grouping, direct trials and one of the students is given a vast opportunity to conduct smaller and effective discussions If there is difficulty for students during learning, they can provide information to each other through questions and answers and look for references in textbook.